Evolutionary properties of the low-luminosity galaxy population in the NGC5044 Group - Buzzoni, A. (2012)
In this third paper of a series we present Johnson-Gunn B, g, V, r, i, z multicolour photometry for 79 objects, including a significant fraction of the faintest galaxies around NGC5044, assessing group membership on the basis of apparent morphology (through accurate Sérsic-profile fitting) and low-resolution (R= 500-1000) optical spectroscopy to estimate the redshift for 21 objects. Early- and late-type systems are found to be clearly separate in Sérsic parameter space, with the well-known luminosity versus shape relation being mostly traced by different morphological types spanning different ranges in the shape parameter n. A significantly blue colour is confirmed for Magellanic irregulars (Sm/Ims), while a drift toward bluer integrated colours is also an issue for dwarf ellipticals (dEs). Both features point to moderate but pervasive star-formation activity even among nominally 'quiescent' stellar systems. Together, dEs and Ims provide the bulk of the galaxy luminosity function, around M(g) ≃-18.0 ± 1.5, while the S0 and dwarf spheroidal (dSph) components dominate the bright and faint-end tails of the distribution respectively. This special mix places the NGC5044 Group just 'midway' between the high-density cosmic aggregation scale typical of galaxy clusters and the low-density environment of looser galaxy clumps like our Local Group. The bright mass of the 136 member galaxies with available photometry and morphological classification, as inferred from appropriate M/L model fitting, amounts to a total of 2.3 × 10 12M ⊙. This is one seventh of the total dynamical mass of the group, according to its X-ray emission. The current star-formation rate within the group turns to be about 23M ⊙yr -1, a figure that may however be slightly increased as a result of the evident activity among dwarf ellipticals, as shown by enhanced Hβ emission in their spectra. Lick narrow-band indices have been computed for 17 galaxies, probing all the relevant atomic and molecular features in the 4300-5800Å wavelength range. Dwarf ellipticals are found to share a subsolar metallicity (-1.0 ≲ [Fe/H] ≲- 0.5), with a clear decoupling between iron and α elements, as already established for high-mass systems. Both dEs and dS0s are consistent with a high age, about one Hubble time, although a possible bias towards higher values of age may be induced by the gas emission affecting the Hβ strength. © 2012 The Authors Monthly Notices of the Royal Astronomical Society